Morphometric Variations of Thyroid Gland: A Cadaeric Study - Bhattarai, Laxmi (Journal of Karnali Academy of Health Sciences, 2023)
Background: The size of thyroid gland is subject to great variations. The thyroid gland consists of two lobes and a bridging isthmus. It is located anteriorly in the neck at the level of the C5–T1 vertebrae deep to the Infrahyoid muscles. The developmental anomalies of the thyroid gland are partial and total agenesis, various ectopic tissues, accessory thyroid, and absence of isthmus. This distorts the morphology of the gland and causes clinical and functional disorders.Methods: The thyroid gland was removed from 28 embalmed cadavers. Specimen of abnormal conditions like enlarged gland, partial and total agenesis of gland and absent isthmus was excluded from the study. Presence of pyramidal lobe and levator glandulae thyroidea was noted. The dimensions of each lobe was measured using Vernier caliper. Descriptive statistics was calculated as mean and standard deviation.Results: The average length (right lobe=4.96cm, left lobe= 4.48cm), width (right lobe=2.25cm, left lobe=1.86cm) and thickness (right lobe=1.53cm, left lobe=1.45cm) were measured. Pyramidal lobe was present in 32.14%. Levator glandulae thyroidea was found in only one case (3.57%).Conclusion: Variation in the dimensions of thyroid gland are reported. Knowledge of the wide ranging variations and measurements will help the surgeons and radiologists in correct interpretation, diagnosis and treatment of thyroid diseases.